2013
DOI: 10.3354/meps10321
|View full text |Cite
|
Sign up to set email alerts
|

Population genetics of the invasive ctenophore Mnemiopsis leidyi in Europe reveal source–sink dynamics and secondary dispersal to the Mediterranean Sea

Abstract: Repeated invasions of European waters by the ctenophore Mnemiopsis leidyi offer a unique opportunity to study population dynamics and dispersal in gelatinous zooplankton. Here we followed population establishment in 2 recently invaded areas, the North and Baltic Seas, and analysed changes in population structure during a 3 yr interval using 7 highly polymorphic microsatellites comprising 191 alleles. A second goal was to reconstruct routes of recent invasive range expansion into the Mediterranean Sea. During t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 66 publications
3
32
2
Order By: Relevance
“…Reusch et al (2010) and Ghabooli et al (2011) concluded that the Gulf of Mexico was the source for the Black Sea invasion while the northern M. leidyi European populations derived from samples at the northern extreme of the ctenophore's range, in New England. A third study using microsatellite data (Bolte et al 2013) indicated that the Mediterranean Sea regions were likely inoculated with animals from the Black Sea. Recently, Ghabooli et al (2013) examined variation in both mitochondrial cytochrome c oxidase I (COI) and nuclear ITS regions, indicating the possibility that Mediterranean populations may have been the result of independent invasion(s) in addition to introduction from the Black Sea.…”
Section: Introductionmentioning
confidence: 97%
“…Reusch et al (2010) and Ghabooli et al (2011) concluded that the Gulf of Mexico was the source for the Black Sea invasion while the northern M. leidyi European populations derived from samples at the northern extreme of the ctenophore's range, in New England. A third study using microsatellite data (Bolte et al 2013) indicated that the Mediterranean Sea regions were likely inoculated with animals from the Black Sea. Recently, Ghabooli et al (2013) examined variation in both mitochondrial cytochrome c oxidase I (COI) and nuclear ITS regions, indicating the possibility that Mediterranean populations may have been the result of independent invasion(s) in addition to introduction from the Black Sea.…”
Section: Introductionmentioning
confidence: 97%
“…The textbook case is the introduction in 1982 of one of the top 100 worst invasive species, according to IUCN, the ctenophore Mnemiopsis leidyi in the Black Sea through ballast waters. The introduction of this strong predator, native to the Gulf of Mexico [119,120], coincided with the collapse of local fisheries. Whether the introduction of this ctenophore is the reason for the collapse or just a collateral event that made things worse is still not clear.…”
Section: Mediterranean Species and Ecosystemsmentioning
confidence: 99%
“…Mnemiopsis leidyi exhibits pronounced source -sink dynamics with local extinctions at less favourable locations combined with repeated annual re-colonization from adjacent seed areas in both its native and introduced ranges (Purcell et al, 2001;Costello et al, 2006Costello et al, , 2012Bolte et al, 2013). During the non-reproductive period, advective losses can result in the disappearance of M. leidyi from large areas (Costello et al, 2006(Costello et al, , 2012.…”
Section: Source -Sink Dynamicsmentioning
confidence: 99%
“…Simultaneously, M. leidyi has also spread to the Mediterranean, most likely through secondary invasion from the Black Sea (Ghabooli et al, 2011;Bolte et al, 2013).…”
Section: Introductionmentioning
confidence: 99%